Pan-mutant IDH1 inhibitor BAY 1436032 for effective treatment of IDH1 mutant astrocytoma in vivo - Pusch, Stefan; Fischer, Viktoria; Ott, Martina; Schrimpf, Daniel; Capper, David; Sahm, Felix; Wick, Wolfgang; Unterberg, Andreas; Herold-Mende, Christel; Platten, Michael; Deimling, Andreas von (Acta neuropathologica, 2017)
Mutations in codon 132 of isocitrate dehydrogenase (IDH) 1 are frequent in diffuse glioma, acute myeloid leukemia, chondrosarcoma and intrahepatic cholangiocarcinoma. These mutations result in a neomorphic enzyme specificity which leads to a dramatic increase of intracellular d-2-hydroxyglutarate (2-HG) in tumor cells. Therefore, mutant IDH1 protein is a highly attractive target for inhibitory drugs. Here, we describe the development and properties of BAY 1436032, a pan-inhibitor of IDH1 protein with different codon 132 mutations. BAY 1436032 strongly reduces 2-HG levels in cells carrying IDH1-R132H, -R132C, -R132G, -R132S and -R132L mutations. Cells not carrying IDH mutations were unaffected. BAY 1436032 did not exhibit toxicity in vitro or in vivo. The pharmacokinetic properties of BAY 1436032 allow for oral administration. In two independent experiments, BAY 1436032 has been shown to significantly prolong survival of mice intracerebrally transplanted with human astrocytoma carrying the IDH1R132H mutation. In conclusion, we developed a pan-inhibitor targeting tumors with different IDH1R132 mutations.